RAGAM PERSPEKTIF PEDAGOGIK: TENTANG MAKNA PENDIDIKAN, PENGAJARAN, DAN PELATIHAN - Syofiyanti, Dessy (Global Action and Education for Society, 2025)
Education is often mistaken for teaching or training, so its holistic aspects are neglected. The curriculum in Indonesia emphasizes more cognition than application and character. This study examines a pedagogic perspective to improve the understanding of holistic education, so that the learning process is more effective and produces individuals who are competent in theory, practice, and morals. This research uses a literature method with a qualitative descriptive approach. The data was analyzed through content analysis to understand the concepts of education, teaching, and training holistically to improve the quality of learning. The results of the discussion were that education shapes students' character mentally, socially, morally, and religiously, while teaching transfers knowledge, and training focuses on job skills. The three are interrelated, but differ in their nature, orientation, and duration of the process. The conclusion that education is the process of humanizing human beings throughout their lives through formal and informal education. Teaching supports education with knowledge, while training develops individual skills. The three are interrelated and become a shared responsibility between the government, society, and family in forming competent individuals.